Redesigned Partnerships as a Result of Redesigned Educational Preparation Program - Gray Smith, Linda; Wood, Sue; Rich, Greg; Singleton, Everett; Wall, Timothy (Educational (Re)naissance, 2020)
This study investigated the ability of a redesigned teacher preparation program to effectively meet the needs of teacher candidates and partner school districts. The study examined the effects of the redesigned school of education program on perceptions of teacher candidates, administrators, teachers in partner districts, and faculty members. Findings from school-partnership districts and the school of education were explored. The goal was to use best practices to meet the needs of teacher candidates and provide rich theoretical and clinical experiences in diverse school settings. Findings indicated a change in perceptions of teacher candidates in understanding the importance of equity in the teaching process and of the connection between theory presented in the classroom and application in settings of diverse learners. Teachers and principals indicated an appreciation for renewal through the collaborative experience with teacher candidates during field experiences.